SPOrT JABAR : SEBUAH PENELITIAN HISTORIS KAITANNYA DENGAN PENGEMBANGAN OLAHRAGA MASA DEPAN - Yedih Lesmana, - (2021)
SPOrT West Java is the only integrated sports development center in West Java Province that uses a pure West Java APBD budget. SPOrT West Java was built with various considerations and struggles in order to optimize sports development in West Java Province. However, there are still many who do not know the history of how the West Java SPOrT was built, how far the West Java SPOrT has contributed to sports development (achievement sports, recreational sports and educational sports) and how the West Java SPOrT plans for the future. So the purpose of this study is to find out the existence of West Java SPOrT in the past, present and future. The qualitative method used in this study uses a historical approach or Historical Research. The research instrument used interviews, observation and documentation studies. The subjects or key informants in this study were those who were directly involved with the development, planning and management of West Java SPOrT. The results showed that: (1) West Java SPOrT was built with great struggle with a large budget to develop an Integrated Sports development center to become a pioneer in the development and progress of Sports in West Java; (2) West Java SPOrT contributes as a place to practice and compete for athletes (achievement sports), increase community participation in sports (recreational sports) and facilitate the existence of a Student Sports Training and Development Center/PPLP (educational sports); (3) SPOrT West Java in the future will continue to develop Sports Science and Technology and infrastructure to support athlete achievement, utilizing the remaining land so that the opportunity for exercise for the community is wider. West Java SPOrT was built in accordance with the concept of integrated green open space city planning in supporting the city's function as a service function, which is equipped with a commercial-service function that can be utilized by city residents. Keywords: West Java SPorT, Sports Development, Achievement Sports, Sports Recreation, Sports Education